1990
DOI: 10.1097/00000658-199004000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Duodenal Ulcer

Abstract: There were 12 hospital deaths in 433 patients (2.8%, 1.6% at 30 days) presenting with bleeding duodenal ulcer. Excluding patients who underwent immediate operation or early elective surgery, where ulcer size was measured at initial endoscopy rebleeding was evident in 40/288 patients (13.9%) and was associated with an increased mortality (0.4% v 12.5%) (p less than 0.0001). Rebleeding rates for ulcers less than or equal to 1 cm and greater than 1 cm were respectively 28/239 (11.7%) and 12/49 (24.5%) (p less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…Our study has also shown that the group of peptic ulcer patients treated with adrenaline injection had a reduction in rebleeding episodes, and this is in accordance with other studies 29 , 30 . As rebleeding is the most important risk factor for death from bleeding ulcer, 31 it is likely that endoscopic treatment does improve the prognosis in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our study has also shown that the group of peptic ulcer patients treated with adrenaline injection had a reduction in rebleeding episodes, and this is in accordance with other studies 29 , 30 . As rebleeding is the most important risk factor for death from bleeding ulcer, 31 it is likely that endoscopic treatment does improve the prognosis in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to certain studies [10,25,26] and consistent with others [18,27], this review did not associate the presence of active bleeding or stigmata of recent hemorrhage with clinically significant rebleeding events. Though more hemorrhagic sequelae accompanied TE than surgical therapy, this difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 41%
“…[ 2 , 3 ] Furthermore, these data are relevant with regard to higher peptic ulcer bleeding (PUB) complications and mortality rate compared with the general population. [ 4 6 ] Moreover, one of the predictors of mortality in validated upper gastrointestinal bleeding scoring systems, such as the Rockall score is renal insufficiency. [ 7 , 8 ] Improvement of outcomes in PUB was attained only after the introduction of interventional endoscopic therapy and high-dose acid suppression.…”
Section: Introductionmentioning
confidence: 99%